2020
DOI: 10.1186/s12909-020-02243-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of panelists’ experience on script concordance test scores of medical students

Abstract: Background The evaluation process of French medical students will evolve in the next few years in order to improve assessment validity. Script concordance testing (SCT) offers the possibility to assess medical knowledge alongside clinical reasoning under conditions of uncertainty. In this study, we aimed at comparing the SCT scores of a large cohort of undergraduate medical students, according to the experience level of the reference panel. Methods In 2019, the authors developed a 30-item SCT and sent it to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“…Similarly to our results, some studies reported that SCT scores also appeared correlated with those obtained on classical MCQ tests for undergraduate students [ 12 ]. In addition, recent large studies carried out within French faculties have confirmed the utility of SCT in the current context with good acceptability from the students' point of view and without any pejorative arguments from the teachers' point of view [ 12 , 33 ].…”
Section: Discussionmentioning
confidence: 73%
“…Similarly to our results, some studies reported that SCT scores also appeared correlated with those obtained on classical MCQ tests for undergraduate students [ 12 ]. In addition, recent large studies carried out within French faculties have confirmed the utility of SCT in the current context with good acceptability from the students' point of view and without any pejorative arguments from the teachers' point of view [ 12 , 33 ].…”
Section: Discussionmentioning
confidence: 73%
“…In this case, it could be better to have panelists with fewer years of experience or with a more general practice. Peyrony et al 25 explored the SCT scores of undergraduate medical students (n = 985) according to the experience level of the reference panel. A panel of 75 experts was divided into three groups: 31 residents, 21 non experienced physicians and 23 experienced physicians.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of having panelists with less than five years of experience was well accepted when the examinees were undergraduate medical students. 25 When the SCT was designed for more experienced examinees such as residents in a broad specialty, such as general surgery or internal medicine, it could be better to have subspecialty-specific experts. 26 This latter recommendation was based on the results of a study by Petrucci et al 26 aiming to determine whether a specialty-specific scoring key improves the validity of the SCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marking of the written questions was undertaken by junior medical officers and senior medical students who had passed their final examinations. The marking of examinations by senior medical students and junior medical officers is a routine approach at certain centres, and has been demonstrated to be effective in a variety of examination formats 11,12 . If an answer was considered reasonable, but was not addressed by the predefined marking criteria, consensus was reached through group discussion.…”
Section: Number Of Marks Model Professionalism Mean Classification Ac...mentioning
confidence: 99%